1989
DOI: 10.1103/physrevlett.63.1145
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated electromagnetic emission near electron cyclotron harmonics in the ionosphere

Abstract: Observations of electromagnetic emission stimulated by a high-frequency radio wave injected into the ionosphere from a ground-based powerful transmitter operated near harmonics of the ionospheric electron cyclotron frequency are reported. Significant changes in the spectrum of the stimulated electromagnetic radiation were obtained as the injected frequency was varied in small steps around these harmonics. The experimental results are attributed to nonlinear wave interactions involving electrostatic wave modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 16 publications
2
110
0
Order By: Relevance
“…The behavior of the BUM relative to the presence or absence of striations is more ambiguous. The BUM appears continuously over a range of pump frequencies starting at -10 kHz below the gyroharmonic frequency [Frolov et al, 1996] and continuing to a maximum frequency (fpmx) --100 kHz above the gyroharmonic frequency [Thid• et al, 1983;Stubbe et al, 1984Stubbe et al, , 1994Leyser et al, 1989Leyser et al, , 1990Leyser et al, , 1993Frolov et al, 1996]. Over this range of pump frequencies, striations are present everywhere except for a narrow range of frequencies surrounding the gyroharmonic frequency.…”
Section: Tionsmentioning
confidence: 99%
“…The behavior of the BUM relative to the presence or absence of striations is more ambiguous. The BUM appears continuously over a range of pump frequencies starting at -10 kHz below the gyroharmonic frequency [Frolov et al, 1996] and continuing to a maximum frequency (fpmx) --100 kHz above the gyroharmonic frequency [Thid• et al, 1983;Stubbe et al, 1984Stubbe et al, , 1994Leyser et al, 1989Leyser et al, , 1990Leyser et al, , 1993Frolov et al, 1996]. Over this range of pump frequencies, striations are present everywhere except for a narrow range of frequencies surrounding the gyroharmonic frequency.…”
Section: Tionsmentioning
confidence: 99%
“…Even if the observed spectra are highly reproducible, they depend strongly on the applied HF frequency. In the work of Leyser et al [1989] it was reported that several of the prominent spectral features are absent when the applied frequency is near a harmonic of the electron gyrofrequency. After that, emphasis has been put on the possible role of smallscale magnetic field-aligned density striations, which are known to be generated in these experiments [Fialer, 1974;Minkoff et al, 1974;Djuth et al, 1985].…”
Section: Introductionmentioning
confidence: 99%
“…Finally the high frequency ES wave scatters from irregularities back into the EM wave measured on the ground. The downshifted maximum (DM), a distinct peak at a frequency approximately 10 kHz below the pump [Leyser, 2001] involving electrostatic lower hybrid waves is believed to be produced through this mechanism [Bernhardt et al, 1994;Huang and Kuo, 1995;Leyser et al, 1989Leyser et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%